2018
DOI: 10.1103/physrevb.97.241403
|View full text |Cite
|
Sign up to set email alerts
|

Valley switch in a graphene superlattice due to pseudo-Andreev reflection

Abstract: Dirac electrons in graphene have a valley degree of freedom that is being explored as a carrier of information. In that context of "valleytronics" one seeks to coherently manipulate the valley index. Here we show that reflection from a superlattice potential can provide a valley switch: Electrons approaching a pristine-graphene-superlattice-graphene interface near normal incidence are reflected in the opposite valley. We identify the topological origin of this valley switch, by mapping the problem onto that of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Valley rotation in the graphene channel relies on Kek-Y graphene superlattice [10][11][12], which can be achieved by a superlattice of graphene grown epitaxially onto Cu(111), with the copper atoms in registry with the carbon atoms [9]. However, copper atoms are lacking under some carbon atoms, resulting in some periodic copper atom vacancies appearing below graphene.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Valley rotation in the graphene channel relies on Kek-Y graphene superlattice [10][11][12], which can be achieved by a superlattice of graphene grown epitaxially onto Cu(111), with the copper atoms in registry with the carbon atoms [9]. However, copper atoms are lacking under some carbon atoms, resulting in some periodic copper atom vacancies appearing below graphene.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a electic barrier are also applied in the Kek-Y lattice region, which can be tuned by external bias voltage. The low-energy excitation quasiparticles propagation in the VFETs with Kek-Y graphene superlattices can be described by the following single particle Hamiltonian [10][11][12]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of both the Kekulé distortions on the electronic and transport properties of graphene have been widely explored, for instance: Wang et al investigated the enhanced valley-dependent Klein tunneling of electrons through a rectangular potential barrier in Kek-Y graphene 9 ; Beenakker et al showed that a potential with a Kekulé modulation can generate pseudo-Andreev reflections, where incoming electrons in a certain valley are reflected in the other 10 ; the nature of valley-dependent currents in Kek-O distorted superconducting heterojunction was recently explored by Wang et al 11 ; also, recent studies by Andrade et al found, and later confirmed experimentally by Eom and Koo 1 , that the uniaxial strain in Kek-Y graphene can separate the Dirac cones away from the Γ-point 12,13 . Other studies include the proposal of a device to control the valley orientation of channel electrons based on the valley precession produced by the Kek-Y texture 14 , as well as the study of the resonant electronic transport in graphene nanoribbons with periodic Kekulé distortions 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Though it should be mentioned that the moiré superlattice potential is always present in both inner and outer regions, only the Fermi level is spatially tuned by the BG and TG to reside within the different bands of the reconstructed band structure (unlike the transition from a nonsuperlattice to superlattice region as, e.g., proposed in Ref. [39]). It is already visible from the maps [Figs.…”
mentioning
confidence: 97%